Prescribing of menopausal hormone therapy in Germany: Current status and changes between 2004 and 2016. Issue 4 (11th January 2021) - Heinig, Miriam; Braitmaier, Malte; Haug, Ulrike
Abstract: Background: Prescribing of menopausal hormone therapy (MHT) declined drastically after publication of the Women's Health Initiative's (WHI) findings in 2002, but studies on longer‐term trends and details of use are scarce. Methods: We used the German Pharmacoepidemiological Research Database (GePaRD) containing health insurance claims data from ~25 million persons. Using data from 2004–2016, we conducted cross‐sectional analyses to determine the prevalence of MHT use overall and by type and route of administration in women aged 45–75. In longitudinal analyses, we assessed MHT use over 5 years and compared the patterns between different time periods. Results: From 2004 to 2016, prevalence of systemic MHT prescriptions decreased by >60% in women aged 55–65 and by >50% in women aged 50 and 70 years old. Prevalence declined for most types and routes of administration at all ages (−16% to −79%) with some exceptions, for example, local MHT (vaginal estrogen). Among 50‐year‐old women in 2012, 6% were already prescribed systemic MHT at age 49 and of the remaining women, 16% were newly prescribed systemic MHT before age 55. At all ages, the cumulative dose of systemic MHT prescribed over 5 years was lower in the period 2012–2016 compared to 2005–2009 (−6% to −46%). Conclusions: For most types of MHT and all age groups, prevalence declined considerably between 2004 and 2016 in Germany. The cumulative dose per MHT user also decreased, suggesting a trend towards a shorter duration of use.